Chitosan Coating Enriched With Ruta graveolens L. Essential Oil Reduces Postharvest Anthracnose of Papaya (Carica papaya L.) and Modulates Defense-Related Gene Expression - Landi, Lucia; Peralta-Ruiz, Yeimmy; Chaves-López, Clemencia; Romanazzi, Gianfranco (Frontiers in Plant Science, 2021)
The fruit of papaya (Carica papaya L.) has several postharvest problems, mainly due to improper storage, packaging, and transportation, that enhance the development to fungal diseases, such as anthracnose. This is caused by Colletotrichum gloeosporioides, and results in rapid softening and reduced shelf-life. Coating with chitosan (CS) and Ruta graveolens essential oil (REO) might represent a novel eco-friendly method to prevent postharvest anthracnose infection. These compounds both show antimicrobial and eliciting activities, although the molecular mechanisms in papaya have not been investigated to date. In this study, the effectiveness of CS and REO alone and combined (CS-REO) on postharvest anthracnose of papaya fruit during storage were investigated, along with the expression of selected genes involved in plant defense mechanisms. Anthracnose incidence was reduced with CS, REO, and CS-REO emulsions after 9 d storage at 25 °C, by 8 %, 21 %, and 37 %, respectively, with disease severity reduced by 22 %, 29 %, and 44 %, respectively. Thus, McKinney’s decay index was reduced by 22 %, 30 %, and 44 %, respectively. A protocol based on qRT-PCR was validated for 17 papaya target genes linked to signaling pathways that regulate plant defense, pathogenesis-related protein, cell-wall-degrading enzymes, oxidative stress, abiotic stress, and the phenylpropanoid pathway. CS induced gene up-regulation mainly at 6 h post treatment (hpt) and 48 hpt, while REO induced the highest up-regulation at 0.5 hpt, which then decreased over time. Furthermore, CS-REO treatment delayed gene up-regulation by REO alone, from 0.5 hpt to 6 hpt, and induced gene up-regulation over time compared to the other treatments. This study suggests that CS stabilizes the volatile and/or hydrophobic substances of highly reactive essential oils. This followed an additive effect of CS and REO, to optimize reduction of both postharvest decay and gene expression in papaya fruit.